Localized pyopneumothorax treated with a vacuum-assisted closure system - Jagelavičius, Žymantas; Vaitėnas, Gediminas; Jovaišas, Vytautas; Janilionis, Ričardas (Lietuvos chirurgija, 2015)
A 52-year-old male was admitted to the Department of General Thoracic Surgery with a right-side localized pyopneumothorax that showed no improvement after conservative treatment. Open-window thoracostomy was created due to the presence of bronchopleural fistula. The capacity of the cavity was 600 ml. On the 11th postoperative day, a spontaneous closure of the bronchopleural fistula occurred. Later, a vacuum-assisted device was used for the residual empyema cavity treatment. It was used for 15 days, sponges were changed every 5 days. The residual cavity reduced in size six times (till 100 ml). The patient was discharged for a daily dressing changing at the outpatient department. After two months the patient was ready for a radical closure of open-window thoracostomy. The postoperative period was uneventful. The case shows that the vacuum-assisted closure therapy can be safely used in open-window thoracostomy after pleural empyema. This method reduces the duration of open-window thoracostomy and accelerates surgical closure.